Perfil lipídico sérico e ede ácidos graxos do tecido adiposo em cadelas com tumores mamários: caso-controle - Sabino, Fabiane Aparecida [UNESP] (2014)
The aim of this study was to analyze comparatively the lipid profile in serum and fatty acid profile in adipose tissue from dogs with and without mammary tumors. Twenty bitches, all healthy, none spayed, and that had non mammary tumor evidence during palpation (control group) and twenty bitches with mammary tumor, already diagnosed using fine needle aspiration cytology, were used in this study. All animals were submitted to anamnesis, general and specific to nutritional and reproductive history. A physical exam was performed in order to determine the body condition of those animals, and in the group of animals with neoplasia, a clinical (TNM) and a histopathology exam were performed in the tumors. To evaluate the serum lipid profile the triglycerides and total cholesterol were measured. Gas chromatography was used to identify methyl esters from fatty acid obtained from abdominal adipose tissue from the dogs during surgery. All fatty acids were expressed in percentage of lipid fraction of each fatty acid in relation to total content in each sample from each animal. Both groups (80%) were fed with commercial dog food adding homemade food. When homemade food was used, usually it was the same prepared for the human consumption, most of them used soy oil to prepare and beef was the most provided kind of protein. None association between obesity, serum total cholesterol levels and triglycerides increasing the risk of development mammary tumors were observed in this study. Total cholesterol and triglycerides serum levels average had higher values in animals that were overweight or morbid obese. Alfa-linoleic (C 18:3) and cis-linoleic acid (C 18:2) levels did not had any difference when comparing control group and tumor group. The proportion of omega6/omega3 in control group was 21:1 and in tumor group it was 23:1. None correlation was found between the fatty acid profile in the adipose tissue with histopathology classification of tumors and ...